The Effect of Premature Sign-off and Under-reporting of Chargeable Time of Audit on The Performance of Auditors - Hossein Rajabdorri; Amirreza Khanizalan (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The purpose of this study is to investigate the effect of premature sign-off and Under-reporting of chargeable time on the performance of auditors. Methodology: This study is a survey-applied. A case study was also conducted through questionnaires and random sampling from 115 active auditors in the country in 2019, both virtual and in person. Structural Equation Modeling was performed using Smart PLS software and a one-sample T-test using SPSS software to analyze the findings using four main hypotheses. Findings: The research findings showed a negative and significant relationship between the premature sign-off and under-reporting of chargeable time and the performance of the auditors and increasing the premature sign-off and under-reporting of chargeable time. Also, in the investigated community, the level of premature sign-off and Under-reporting of chargeable time is not good. Originality/Value: Regarding the findings, which confirmed the effect of auditors' behavior on their performance, it is necessary to make robust decisions to guide the behavior of auditors to understand and control the behavior of auditors to understand better and plan.